United Irishmen in Training. - Gillray, James, 1756-1815 (Humphrey, H., 1798)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; United Irishmen; Ireland -- History -- Rebellion of 1798